Solubility Enhancement of Oxcarbazepine by Melt Sonocrystallization Technique to Increase the Bioavailability - Mastiholimath, Vinayak Shivamurthy; Mashelkar, Gauri Pradeep; Mannur, Vinodkumar Shirshalappa; Dandagi, Panchaxari Mallappa; Khanal, Pukar (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: The present study aimed to enhance the solubility of Oxcarbazepine by melt sono crystallization technique as well as increase its bioavailability. Materials and Methods: Tablets of Melt Sonocrystallized Oxcarbazepine were prepared by the direct compression method. Compression was performed on a Remik mini-press tablet compression machine using an 8mm punch. The analytical method development was carried out in 20x10 and 10x10 twin trough chambers. The sample was spotted with a 100μl camas microliter syringe on silica gel aluminum plate 60 F254 (20X10) and (10x10) plate; Merck using a CAMAG Linomat-5 sample applicator. Results: The Oxcarbazepine had better solubility in the ph 6.8 buffer. The mobile phase selected for HPTLC was Ethyl acetate: Methanol in the ratio (8:2 v/v) with the Rf value 0.582. The formulation F2 containing 5% SSG showed a release of 90.51% and was considered as an optimized formulation based on several parameters such as friability (0.21%), disintegration time(27.8 sec) and in vitro dissolution studies.
Keywords: Melt sonocrystallized; Oxcarbazepine; Method development; HPTLC; Validation; Solubility Enhancement